Spatial distribution and diversity inventory of macro-benthic fauna in the Indian Sundarban - Sau, Susovan; Nagesh, T. S.; Trivedi, R. K.; Abraham, T. J.; Dubey, S. K.; Rout, S. K.; Biswas, I.; Bhakta, Dibakar (Indian Journal of Fisheries, 2021)
In the present study, an attempt was made to document the spatial distribution and Â diversity inventory of macro-benthic fauna from 21 sampling stations of the Indian Sundarbanfor a period of six months from November 2014 to April 2015. A total of 1,871 individuals belonging to 35 species were recorded which comprised 12 species of molluscs, 20 species of crustaceans, one species each of xiphosurid, sea anemone and fish. The frequency analysis of species revealed that the most dominant species were Telescopium telescopium and Tubuca rosea among molluscs and crustaceans, respectively. The density analysis of the species showed that Â Pirenella cingulata and T. rosea had maximum values among molluscs and crustaceans, respectively. The average values of Shannon-Wiener diversity index, Simpson diversity index, dominance index and Margalef diversity index were found to be 2.712, 0.888, 0.111 and 4.513, respectively.Keywords:Indian Sundarban, Macro-benthic fauna, Spatial distribution, Species diversity